PENGARUH PENDAPATAN ASLI DAERAH DAN DANA ALOKASI UMUM, TERHADAP BELANJA MODAL DENGAN PERTUMBUHAN EKONOMI SEBAGAI VARIABEL PEMODERASI (Studi Pada Pemerintah Kabupaten/Kota di Jawa Tengah) - Eka Sri Wahyuni, 14.05.52.0295; Jaeni, Jaeni (Students Journal of Accounting and Banking, 2018)
This study aims to analyze empirically about the influence of local revenue (PAD), general allocation fund (DAU), to capital expenditure with economic growth (PE) as moderator variable at Regency and City in Central Java Province 2013-2016. Economic Growth in this study is proxied with Gross Regional Domestic Product (GRDP). Population in this research is all Regency and City in Central Java Province. This research data in the form of secondary data in the form of Realization Report of APBD and Central Java Province PDRB table year 2013-2016. The analysis technique usedis Moderated Regression Analysis (MRA). The data that have been collected is analyzed first by testing the classical assumption and then done hypothesis testing with SPSS 19.0. Based on the results of research can be concluded that the Original Revenue does not affect the Capital Expenditure. General Allocation Funds have a significant positive effect on Capital Expenditure. The direction of the regression coefficient is positive, meaning that the increase of General Allocation Fund will increase Capital Expenditure. Economic growth has no effect on Capital Expenditure. Economic growth does not moderate the relationship of the Original Revenue with Capital Expenditure. Economic growth does not moderate the relationshipof general allocation funds with Capital Expenditures.Keywords: Local Revenue, General Allocation Fund, Capital Expenditure and Economic Growth